The Effectiveness of Environmental Legislation in Supporting Sustainable Development Pathways - Emran Mukhtar Abdulsalam Hadeedan (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
supporting sustainable development pathways. It analyzes the conceptual and legal framework governing the relationship between environment and development, and examines the extent to which the national legislative system aligns with international normative transformations resulting from the Stockholm Conference (1972), the Rio Conference (1992), and the 2030 Sustainable Development Agenda. The study adopts a descriptive-analytical approach, supported by systems analysis, to examine the preventive and deterrent tools adopted by the Libyan legislator, including environmental licensing systems, absolute and relative prohibitions of harmful activities, environmental impact assessment (EIA), and the framework of criminal, financial, and administrative sanctions. The findings reveal that Libyan environmental legislation—particularly Law No. (15) of 2003 on Environmental Protection and Improvement—establishes a relatively integrated legal structure combining prevention, regulation, and sanction mechanisms. This reflects a legislative awareness of the need to integrate environmental considerations into development decision-making. Furthermore, the institutional framework, represented by the Environmental General Authority and judicial and supervisory bodies, constitutes a regulatory foundation for protecting natural resources. However, the study identifies a gap between legislative provisions and their practical implementation due to institutional and enforcement challenges. It concludes that strengthening sustainability in Libya requires not only legislative reform but also effective implementation within an integrated vision that balances economic growth with the protection of the rights of future generations to a healthy environment.